Assessment of poisoning survivor cases at a tertiary care teaching hospital - Shakya, Arbin; Acharya, Jenash; Ranjitkar, Malshree; Lama, Geshu; Pandey, Anwit Raj; KC, Aashish (Journal of Kathmandu Medical College, 2021)
Background: Poisoning is one of the most common causes of increased morbidity and mortality worldwide and also one of the common causes of Emergency Department visits. It has now become a major public health issue. Objectives: To assess the poisoning survivor cases and various associated parameters like most common poison, the circumstance of poisoning, age and gender distribution, and triggering factors.Methods: A retrospective study was done in 94 cases of poisoning, from whom reliable history could be obtained, admitted to Kathmandu Medical College, over the period of 12 months, from April 2019 to March 2020. After obtaining ethical clearance secondary data were collected from the medicolegal examination reports. The data were entered and analysed in Statistical Package for Social Sciences (SPSS) v.18.Results: Majority of the victims were females (9, 62.8%), mostly homemakers (31, 33%). The mean age of the population was 30.35 ± 13.48 years and median age 26 years. Organophosphorus was the most frequent agent (44, 46.8%). The commonest triggering factor was a quarrel with family members (56, 65.1%) and in most cases the agent was already present in their home. The act of poisoning was impulsive in these cases. Conclusion: In this study, the most common agent causing poisoning was still organophosphorus which was already present in their homes. Most poisoning cases were intentional. Females especially homemakers were the most common victims. Cases of poisoning can be reduced if the authorities properly monitor the buying and selling of these common agents of poisoning.